A Mass Spectrometry Assay to Simultaneously Analyze ROS1 and RET Fusion Gene Expression in Non–Small-Cell Lung Cancer. Issue 2 (February 2015) - Wijesinghe, Priyanga; Bepler, Gerold; Bollig-Fischer, Aliccia
Abstract : Introduction: ROS1 and RET gene fusions were recently discovered in non–small-cell lung cancer (NSCLC) as potential therapeutic targets with small-molecule kinase inhibitors. The conventional screening methods of these fusions are time-consuming and require samples of high quality and quantity. Here, we describe a novel and efficient method by coupling the power of multiplexing polymerase chain reaction and the sensitivity of mass spectrometry. Methods: The multiplex mass spectrometry platform simultaneously tests samples for the expression of nine ROS1 and six RET fusion genes. The assay incorporates detection of wild-type exon junctions immediately upstream and downstream of the fusion junction to exclude false-negative results. To flag false-positives, the system also comprises two independent assays for each fusion gene junction. Results: The characteristic mass spectrometric peaks of the gene fusions were obtained using engineered plasmid constructs. Specific assays targeting the wild-type gene exon junctions were validated using complimentary DNA from lung tissue of healthy individuals. The system was further validated using complimentary DNA derived from NSCLC cell lines that express endogenous fusion genes. The expressed ROS1-SLC34A2 and CCDC6-RET gene fusions from the NSCLC cell lines HCC78 and LC-2/ad, respectively, were accurately detected by the novel assay. The assay is extremely sensitive, capable of detecting an event in test specimens containing 0.5% positive tumors. Conclusion: The novel multiplexed assay is robustly capable of detecting 15 different clinically relevant RET and ROS1 fusion variants. The benefits of this detection method include exceptionally low sample input, high cost efficiency, flexibility, and rapid turnover.